Learning strategy, learning motivation and parent support to untalented students and students with sports talent - Malec, D.; Niksic, E. (Acta Kinesiologica, 2015)
The main goal of the research was to determine if there were significant differences between untalented students and students with sport talentt in cognitive learning strategies, learning motivation and parent support as these variable had been considered by a number of authors as important personality and environmental factors for talent development in a variety of domains including sport. The samples used in the research were groups of N=30 students talented for team sports, N=23 students talented for individual/duel sports and N=7 untalented (control group). Students from the three groups were attending VII, VIII i IX grades in primary schools of Sarajevo County. The three groups of examinees were equal with respect to their school achievement (grades) and school conduct. On the account of the collected data, analyses showed that there were no differences between students talented for individual/duel sports and team sports (both groups taken together) and untalented students in values of each of the analyzed variable. On the other hand, when the sort of sport was taken into account, the analyses showed that the students talented for individual/duel sports had the highest and the students talented for team sports had the lowest values in cognitive strategies of rehearsal, organization and critical thinking. The talented for individual/duel sports had the highest values and untalented students had the lowest values of intrinsic motivation and task value. No differences were found among the three groups in extrinsic motivation and parent suport.